We have
![\ln \mleft(-x+1\mright)-ln\mleft(3x+5\mright)=ln\mleft(-6x+1\mright)](https://img.qammunity.org/2023/formulas/mathematics/college/2oflg7ehm5l7qxn7rbxcge7xgj2te49mbn.png)
We need to simplify by applying logarithms rules
![\ln \mleft(-x+1\mright)=ln\mleft(-6x+1\mright)+ln\mleft(3x+5\mright)](https://img.qammunity.org/2023/formulas/mathematics/college/j2xceg3rpc8oyloijemtv7xan77i9em0cz.png)
![ln(-x+1)=\ln ((-6x+1)(3x+5))](https://img.qammunity.org/2023/formulas/mathematics/college/z0c9d0n1to07y8i3pv7h7szlhjwl9km7vr.png)
Then we apply the exponential on both sides
![-x+1=(-6x+1)(3x+5)](https://img.qammunity.org/2023/formulas/mathematics/college/h3v5l8txpiwubwr6y8bqsl9jsp1v6g3jux.png)
We simplify
![18x^2+26x-4=0](https://img.qammunity.org/2023/formulas/mathematics/college/1nbfatqig3jid2wkpi098fnkimrqlb9oit.png)
Then we solve the second equation degree with the general formula
![x_(1,2)=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/li72dimqx1poek8bdg3bs589861h83kfxl.png)
where
a=18
b=26
c=-4
we substitute the values
![x_(1,2)=\frac{-26\pm\sqrt[]{(26)^2-4(18)(-4)}}{2(18)}](https://img.qammunity.org/2023/formulas/mathematics/college/iefsfrjz7bqzzhuriougwhhdb05eih3jy7.png)
![x_(1,2)=\frac{-26\pm2\sqrt[]{241}}{36}](https://img.qammunity.org/2023/formulas/mathematics/college/8jxjgiderk9x2ow23s3laygk18zfhy7rvw.png)
We reduce and the solution is
![x_1=\frac{-13+\sqrt[]{241}}{18}=0.14](https://img.qammunity.org/2023/formulas/mathematics/college/9g753h0s0q1dnd5ge6kzm5skny2tss5fl7.png)
![x_2=\frac{-13-\sqrt[]{241}}{18}=-1.58](https://img.qammunity.org/2023/formulas/mathematics/college/9tqspz6rnu1t4yoo8srd1iskl77fy1okfq.png)
ANSWER
–1.58 or 0.14